Characteristics and prognosis of hepatic cytomegalovirus infection in children: 10 years of experience at a university hospital in Korea - Chae-Yeon Min; Joo Young Song; Su Jin Jeong (Korean Pediatric Society, 2017)
PurposeStudies on cytomegalovirus (CMV) infections in immunocompetent children are lacking, and minimal information is available in the medical literature on hepatic manifestations and complications of CMV. The aims of this study were to evaluate the clinical characteristics, laboratory data, and prognosis of children with CMV hepatitis, and to investigate its prevalence at a single medical center in Korea over a 10-year period.MethodsOne hundred thirty-two children diagnosed with CMV infection based on specific markers (anti-CMV IgM, CMV polymerase chain reaction in blood and urine, or CMV culture of urine) were included in the study. Clinical and biochemical characteristics, immunological markers, and outcomes of hepatic CMV infection were determined.ResultsThe median age of patients (n=132) was 8.5 months (range, 14 days-11.3 years). Peak total bilirubin and alanine aminotransferase levels in serum ranged from 0.11-21.97 mg/dL, and 5-1,517 IU/L, respectively. Alanine aminotransferase remained elevated from 2-48 weeks. Jaundice was the most common clinical feature of hepatic CMV infection during infancy. The hematologic findings revealed anemia, leukocytosis, and monocytosis in CMV-infected patients. All participants recovered without administration of ganciclovir.ConclusionIn children with CMV hepatitis, fever was the most common symptom at presentation, and jaundice was the most common clinical feature of hepatic CMV infection in infants younger than 3 months of age. Hepatic CMV infection in immunocompetent children is often a self-limited illness that does not require antiviral therapy, as most patients in this study had favorable outcomes.